2007
DOI: 10.1002/ffj.1778
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition of Achillea lingulata and A. umbellata

Abstract: The composition of the essential oils of Achillea lingulata and A. umbellata were analysed by GC and GC-MS. Among the determined constituents, borneol, bornyl acetate, camphor, α α α α α-and β β β β β -thujone, and 1,8-cineol were found as the main components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 24 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…The identification of the compounds was based on comparison of their retention indices, retention times and mass spectra with those from Wiley libraries spectra, the National Institute of Standards and Technology (NIST)/ National Bureau of Standards (NBS) and literature data. 10,11 The methanolic extract of L. salmonicolor was chromatographed over Silica gel 60H column and eluted with cyclohexane-CH 2 Cl 2 (100:0/0:100) and CH 2 Cl 2 -MeOH (100:0/50:50) to give fractions A-K. Fractions E-G, which were eluted with CH 2 Cl 2 -MeOH (99:1/95:5), were combined and subjected to MPLC chromatography over silica gel with CH 2 Cl 2 -MeOH (100:0/85:15) to give compound 1 (4.9 mg), compound 2 (5.7 mg) and compound 3 (8.1 mg). The more polar fractions H-K, eluted with CH 2 Cl 2 -MeOH (98:2/90:10), were combined and subjected to MPLC chromatography over silica gel with CH 2 Cl 2 -MeOH (100:0/80:20) to give 14 fractions.…”
Section: Fractionation Isolation and Identification Of Compoundsmentioning
confidence: 98%
“…The identification of the compounds was based on comparison of their retention indices, retention times and mass spectra with those from Wiley libraries spectra, the National Institute of Standards and Technology (NIST)/ National Bureau of Standards (NBS) and literature data. 10,11 The methanolic extract of L. salmonicolor was chromatographed over Silica gel 60H column and eluted with cyclohexane-CH 2 Cl 2 (100:0/0:100) and CH 2 Cl 2 -MeOH (100:0/50:50) to give fractions A-K. Fractions E-G, which were eluted with CH 2 Cl 2 -MeOH (99:1/95:5), were combined and subjected to MPLC chromatography over silica gel with CH 2 Cl 2 -MeOH (100:0/85:15) to give compound 1 (4.9 mg), compound 2 (5.7 mg) and compound 3 (8.1 mg). The more polar fractions H-K, eluted with CH 2 Cl 2 -MeOH (98:2/90:10), were combined and subjected to MPLC chromatography over silica gel with CH 2 Cl 2 -MeOH (100:0/80:20) to give 14 fractions.…”
Section: Fractionation Isolation and Identification Of Compoundsmentioning
confidence: 98%
“…Alkanes were used as reference points in the calculation of relative retention indices (RI). The RI were experimentally determined using the standard method involving retention time of n-alkanes [Alkane Standard Solution (04070, 04071), (C 8 -C 20, C [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ), Standard for GC, Fluka, USA], injected after the essential oil under the same chromatographic conditions (18). The RIs of the compounds, determined using C 8 -C 22 as external references, were compared with the published data (19,20).…”
Section: Identification Of Chemical Compoundsmentioning
confidence: 99%
“…The RIs of the compounds, determined using C 8 -C 22 as external references, were compared with the published data (19,20). Especially, several compounds were identified with those of the literature (21)(22)(23)(24), and identification based on co-injection with authentic compounds (Acoros, Sigma-Aldrich, MO, USA). The quantification of each individual volatile flavor components was performed based on the ratio of the peaks obtained from the mass total ion chromatogram and also marked quality percentage of the volatile flavor compounds from the MS data.…”
Section: Identification Of Chemical Compoundsmentioning
confidence: 99%
“…[15] Similar to previous studies [16] , 1, 8-cineole was found to be the major constituent of the oil Achillea tenuifolia, while others reported camphor as the major constituent of this oil. [17] It has been reported that the chemical compositions of the essential oil are highly influenced by climatic conditions and geographical factors. [18,[21][22] …”
Section: Chemical Composition Of the Essential Oilsmentioning
confidence: 99%